2012
DOI: 10.1080/17470218.2011.608854
|View full text |Cite
|
Sign up to set email alerts
|

Whichever way you Choose to Categorize, Working Memory Helps you Learn

Abstract: There has been growing interest in the relationship between the capacity of a person's working memory and their ability to learn to categorize stimuli. While there is evidence that working memory capacity (WMC) is related to the speed of category learning, it is unknown whether WMC predicts which strategies people use when there are multiple possible solutions to a categorization problem. To explore the relationship between WMC, category learning, and categorization strategy use, 173 participants completed two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(104 citation statements)
references
References 79 publications
11
84
9
Order By: Relevance
“…Thus, even if exemplar processes rely on controlled retrieval (e.g., Karlsson et al, 2008), they appear to require less working memory than a rule-based strategy. This result may contradict previous findings that working memory helps solve different judgment and categorization tasks (Craig & Lewandowsky, 2012;Lewandowsky, 2011;Lewandowsky et al, 2012;Weaver & Stewart, 2012).…”
Section: The Influence Of Memory Abilities On Exemplar-based Strategiescontrasting
confidence: 99%
“…Thus, even if exemplar processes rely on controlled retrieval (e.g., Karlsson et al, 2008), they appear to require less working memory than a rule-based strategy. This result may contradict previous findings that working memory helps solve different judgment and categorization tasks (Craig & Lewandowsky, 2012;Lewandowsky, 2011;Lewandowsky et al, 2012;Weaver & Stewart, 2012).…”
Section: The Influence Of Memory Abilities On Exemplar-based Strategiescontrasting
confidence: 99%
“…This result is only partially in line with recent work in the area of categorization. Although a benefit of WMC for learning category structure is generally found, stable individual preferences for strategy use seem mostly unrelated to cognitive abilities such as WMC or reasoning (Craig & Lewandowsky, 2012; J. L. Little & McDaniel, 2015). One important difference between typical categorization tasks and most function learning or process prediction paradigms may be that the latter strongly suggest the existence of an underlying numerical rule.…”
Section: Discussionmentioning
confidence: 99%
“…A number of theoretical accounts of category learning suggest that the acquisition of new categories is a complex activity that may involve a series of specific cognitive abilities or processes (e.g., Ashby & Maddox, 2011;Ashby & O'Brien, 2005). Several recent studies have indicated that working memory plays an important part in category learning (e.g., Craig & Lewandowsky, 2012DeCaro, Carlson, Thomas, & Beilock, 2009;DeCaro, Thomas, & Beilock, 2008;Erickson, 2008;Lewandowsky, 2011;Lewandowsky, Yang, Newell, & Kalish, 2012;Sewell & Lewandowsky, 2012). However, those studies were complicated by the complexity of working memory which is not a unitary construct but consists of multiple components or processes (Baddeley, 1986;Miyake et al, 2000), and it remains unclear which specific processes are involved in category learning.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity associated with the course of acquiring new categories raises the question of what key processes contribute to the performance in category learning. A few empirical studies have already been conducted to identify the key processes by considering a range of cognitive abilities and processes such as attention (Sewell & Lewandowsky, 2012), semantic memory (Ashby & O'Brien, 2005), and working memory (Craig & Lewandowsky, 2012, among which working memory has received the most attention.…”
Section: Introductionmentioning
confidence: 99%